Explaining counter terrorism in the UK: normal politics, securitised politics or performativity of the neo-liberal state?. Issue 3 (3rd July 2019) - Lister, Michael
ABSTRACT: This paper seeks to explore the politics of counterterrorism in the UK. It argues that for a number of reasons, counterterrorism policy has been separated off from other policy areas and seen as securitised, exceptional or just different. The paper argues that such a separation from "normal" politics is problematic, both conceptually and empirically. It argues that much can be gained by considering counterterrorism policy through the lenses, concepts and debates which feature in other areas of British politics. The paper then examines two such lenses/debates – depoliticisation and neo-liberalism. An argument is developed that counterterrorism policy is not, in the main, depoliticised, but rather overt, politicised and visible. This prominence, it is argued, is due to the ways in which neo-liberalism has reduced many of the traditional roles of the state. Drawing on the work of Wacquant and Hall, the paper argues that in the absence of such traditional roles, counterterrorism offers the state an opportunity to perform its own "stateness", to visibly display its sovereign power in a context of ever more (self-imposed) diminished powers.